PEMBELAJARAN MENULIS TEKS ULASAN BERORIENTASI PADA UNSUR PEMBANGUN MENGGUNAKAN METODE BRAINWRITING BERBANTUAN MEDIA FILM BISU PADA PESERTA DIDIK KELAS VIII - Nabila Putri Gunawan; Dindin Zaenal Muhyi; Eggie Nugraha (STKIP Subang, 2024)
This research is motivated by the low ability of students in writing review texts. The factors that cause this is the lack of confidence to pour ideas, ideas thoughts into writing, as well as the ineffectiveness of the learning methods used by educators. One of the learning method that can improve students' ideas and thoughts is the brainwriting method. The purpose of this research is to describe the ability of students in learning to write element-oriented review texts using the brainwriting method assisted by silent film media and to compare the differences in the ability of students in experimental and control classes in learning to write element-oriented review texts using the brainwriting method assisted by silent film media.This research uses a quasi-experimental method with an pre-test and post-test design. The results showed that students' abilities improved in learning to write review texts oriented to the building blocks. There was an increase in the average from 26.5 to 91.4 in the experimental class pretest. There is a significant difference between the learning outcomes of students in the experimental and control classes, with an average post-test score of 91.4 while the control class is 44.1.